PENGARUH CUITAN VIRAL RIDWAN KAMIL TERHADAP OPINI PUBLIK & ELEKTABILITAS PADA PILKADA DKI JAKARTA 2024: KAJIAN ETNOGRAFI VIRTUAL DAN READER RESPONSE - Mahara Haq, Tsanaa; Muthmainnah, Robi’atul; Penggalih, Aura Zahradiva; Dilsari, Alma Shafifa; Darmayanti, Nani (Metahumaniora, 2026)
This study aims to analyze the impact of tweets on the @ridwankamil account on voter decisions in the 2024 DKI Jakarta Pilkada. Using virtual ethnography and reader response methods, this research explores the full range of social media users responses and resulting influences. Equipped with descriptive qualitative methods, this method focuses on discussing in detail by creating a descriptive picture. The results are shown with virtual ethnographic analysis, through four levels, including the media space level, media document level, media object, and experience level. These levels are processed and show the conclusion that the tweets uploaded by Ridwan Kamil in the past caused scathing criticism directed at the DKI Jakarta regional head candidates. Of the 13 data of Ridwan Kamil's tweets on social media X used, all of them received 29,597 likes, 31,054 reposts, 5,535 quotes, and 2,837 comments. These data at the experiential level were analyzed using the reader response approach. This analysis was proven through a survey with the results of 35 respondents. Respondents who represent a sample of the community as well as voters in the 2024 DKI Jakarta Pilkada strongly agreed (51.4%) with the majority of the public or netizen X's protest against Ridwan Kamil's tweets.